1997
DOI: 10.1136/hrt.78.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancies in patients with complex pulmonary atresia.

Abstract: Objective-To evaluate the outcome of pregnancies in patients with complex pulmonary atresia, comparing those with and without previous radical surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Maternal mortality with pulmonary atresia is reported to be low with only two maternal deaths reported [5,6]. There is lack of evidence regarding the optimal time and mode of delivery in these patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Maternal mortality with pulmonary atresia is reported to be low with only two maternal deaths reported [5,6]. There is lack of evidence regarding the optimal time and mode of delivery in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…Two case series, comprising 14 patients of TOF with pulmonary atresia with no corrective surgery, report a total of 35 pregnancies with successful pregnancy outcomes in 10 cases with live birth rates of 51 and 44 %, respectively [4,5]. Presbitero concluded that the probability of live birth could be predicted by hemoglobin of [20gm % and saturation \85 %.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal Hb level and SpO 2 showed a significant relationship to fetal outcomes, with a higher maternal Hb and lower SpO 2 correlating with more pregnancy losses. In a large series of pregnancies in patients with maternal complex pulmonary atresia (a related cardiovascular physiologic process), Neumayer and Somerville provided details of 41 pregnancies in 15 patients [7]. Of the total 41 pregnancies, there were 23 live births; two of these neonates subsequently died.…”
Section: Discussionmentioning
confidence: 97%
“…This is often the case in the following situations: operated tetralogy of Fallot, right ventricle to pulmonary conduits used to repair truncus arteriosus or pulmonary atresia with ventricular septal defect (VSD), or repaired malposition of the great arteries with VSD. This situation is often well tolerated, even in cases of severe pulmonary regurgitation, and delivery might be normal 8. The fear of ventricular or atrial arrhythmia can sometimes lead to pre-pregnancy pulmonary valve replacement, if the functional status before pregnancy is greatly impaired.…”
Section: Palliated or Balanced Heart Defectmentioning
confidence: 99%